2003
DOI: 10.1007/s00441-002-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of epidermal growth factor and epidermal growth factor receptor on hemidesmosome complex formation and integrin subunit β4

Abstract: Epidermal growth factor (EGF) stimulates integrin b4 expression and synthesis in corneal epithelium through ligand binding to the EGF receptor, receptor dimerization and activation of the intracellular domain. We hypothesized that inhibition of EGF receptor messenger RNA (mRNA) would block integrin b4 expression, which is induced by EGF. We also tested the hypothesis that EGF would cause the degradation of hemidesmosomes in control and injured corneal organ cultures. Primary rabbit corneal epithelial cell cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…EGF receptors are upregulated following corneal injury [ 20 , 44 , 45 ]. We proposed that the EGF response might mediate the rate of wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…EGF receptors are upregulated following corneal injury [ 20 , 44 , 45 ]. We proposed that the EGF response might mediate the rate of wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Other functions of EGF, such as modulation of cell migration, adhesion, and immune response, might also be present. 27,28 Goblet cells are highly specialized epithelial cells located in the apical surface of the conjunctiva. The main functions of goblet cells are synthesizing, storing, and secreting MUC5AC for the mucous component of the tear film.…”
Section: Discussionmentioning
confidence: 99%
“…The repair requires a controlled and collaborative system of communication between epithelial and neuronal cells to resynthesize the damaged matrix [1], [2], migrate into the wound bed [3]–[5], and return the epithelium to its original architecture. Previous studies have shown that damage to corneal epithelial cells results in release of nucleotides into the extracellular space at the wound site [6][8].…”
Section: Introductionmentioning
confidence: 99%